BP[dG]-induced distortions to DNA polymerase and DNA duplex: A detailed mechanism of BP adducts blocking replication. (June 2020) - Wu, Zhixiang; Peng, Lianxin; Hu, Yichen; Xie, Tao; Yan, Hailian; Wan, Hua; Liu, Wei; Liang, Li; Xie, Zhenjian; Liu, Kunping; Shi, Hubing; Zhao, Gang; et al.
Abstract: As one of the most widespread environmental pollutants, benzo[α]pyrene is metabolized to diol epoxides and then covalently breaks the initial DNA base pairs, which has been closely related to the occurrence and development of many human cancers. High fidelity DNA polymerases play an extremely important role in maintaining the reliability or fidelity of nucleic acid replication, which is generally blocked by BP adducts. To reveal the blocking mechanism of BP, two comparative molecular dynamics simulations were performed for the thermophilic Bacillus stearothermophilus DNA polymerase I large fragment (BF) complexes with normal and BP-bound DNA duplexes. The results of global conformational changes and molecular interactions show that the association of BP leads to the rearrangement of intramolecular hydrogen bonds, impairing the molecular recognition between the polymerase and the DNA duplex. It is also found that the conformation of DNA duplex is distorted, accompanied by an increase in molecular overall rigidity. In terms of possible blocking mechanisms, the BP moiety perfectly integrates itself into the base-paired environment in a special vertical conformation and occupies the space required for the incoming nucleotide. This work provides useful dynamics and structural information for understanding the toxic effect of BP on DNA replication at atomic level. Highlights: Association of BP leads to the rearrangement of intramolecular hydrogen bonds. Molecular recognition between polymerase and DNA duplex is impaired. Conformation of DNA duplex is distorted, accompanied by an increase in molecular overall rigidity. Force field of [BP]dG is established based on different RESP charges.